Sharpening Accounting Skills with Games: A Literature Review on Game-Based Accounting Learning - Srimaryani Srimaryani; Riyan Yuliyanto; Rizka Andriyati (RIRAI Publisher, 2023)
This research aims to provide a comprehensive literature review on the use of games in accounting learning, both in manual and digital formats. Currently, students experience a decline in concentration when learning accounting concepts, necessitating more engaging and practical learning alternatives. Therefore, many educators have begun developing games relevant to accounting education to address this issue. This article is a Systematic Literature Review (SLR). The study explores 17 articles on accounting games (both manual and digital) published in accounting journals in the Scopus database over a period of 2002 to 2022. Through this research, the author aims to provide a quick reference for accounting educators to gain insights into the types of games available to enhance students pedagogical abilities. In this study, the author strives to provide as comprehensive details as possible regarding the games and activities that can be conducted in accounting learning. It is hoped that this research can assist educators in developing more effective and enjoyable learning methods for students.